2015
DOI: 10.1002/phar.1619
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Quetiapine Treatment on Duration of Hypoactive Delirium in Critically Ill Adults: A Retrospective Analysis

Abstract: In this mixed ICU population, treatment of hypoactive delirium with quetiapine was safe and reduced the duration of delirium compared with standard care alone. Prospective placebo-controlled studies are needed to further assess the role of antipsychotics in hypoactive delirium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 46 publications
(78 reference statements)
3
26
1
Order By: Relevance
“…Also, antipsychotics used to prevent and treat delirium were recognized as potential risk factors for ARDS . Thus the toolkit for managing ICU delirium in patients with ARDS should use a multimodal approach utilizing early nonpharmacologic and pharmacologic interventions to prevent ICU delirium and decrease the severity of delirium in patients who develop it during their hospital course . Patients should be carefully screened for ICU delirium because hyperactive and hypoactive delirium do not often occur in isolation, and hypoactive delirium is associated with more detrimental outcomes .…”
Section: Delirium In Ardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, antipsychotics used to prevent and treat delirium were recognized as potential risk factors for ARDS . Thus the toolkit for managing ICU delirium in patients with ARDS should use a multimodal approach utilizing early nonpharmacologic and pharmacologic interventions to prevent ICU delirium and decrease the severity of delirium in patients who develop it during their hospital course . Patients should be carefully screened for ICU delirium because hyperactive and hypoactive delirium do not often occur in isolation, and hypoactive delirium is associated with more detrimental outcomes .…”
Section: Delirium In Ardsmentioning
confidence: 99%
“…Finally, in a retrospective analysis of medical and surgical ICU patients with hypoactive delirium who received either quetiapine or no intervention, quetiapine reduced the duration of delirium, and there was a trend toward decreased duration of mechanical ventilation. Interestingly, quetiapine was initiated earlier in the patients who had a shorter duration of delirium, and a shorter duration of delirium was associated with significantly shorter durations of mechanical ventilation and ICU and hospital lengths of stay .…”
Section: Antipsychotics For Delirium Treatmentmentioning
confidence: 99%
“…Quetiapine is an atypical antipsychotic drug, which has been shown to be effective in the treatment of mental health conditions. It is also widely used in ICUs because of its efficacy in treating ICU delirium [2,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The evidence for utilizing antipsychotics to improve outcomes in patients with ICU delirium remains limited. 15,[17][18][19][20] Only one study has demonstrated a reduction in the duration of delirium in critically ill patients, although this was a small study of only 36 patients treated with quetiapine. 17 No study to date has found a significant reduction in mortality.…”
mentioning
confidence: 99%